Аналіз фотограметрії як методу створення 3d-моделей - Багаєва, М. А. (ХНУРЕ, 2024)
Photogrammetry remains in today's world, offering precision, flexibility, and efficiency in creating 3D models from 2D images. It's especially vital for cultural heritage preservation, endangered by time, disasters, or human activities. Additionally, drones and software advancements make photogrammetry more accessible and effective, transforming images into 3D models for various applications. This process, based on principles of digital imaging and photogrammetry, involves subtracting space to isolate objects for detailed processing or analysis.
Keywords: фотограметрія; створення 3d-моделей